The influence of land surface temperature on Ghana’s climate variability and implications for sustainable development - Collins Oduro; Kenny Thiam Choy Lim Kam Sian; Daniel Fiifi Tawia Hagan; Hassen Babaousmail; Brian Odhiambo Ayugi; Yanjuan Wu; Tatenda Dalu; Naicheng Wu (Scientific Reports)
Abstract Climate change poses significant global challenges, especially in the West African sub-region, with high temperature and precipitation patterns variability, threatening socio-economic stability and ecosystem health. While global factors such as greenhouse gases and oceanic circulations shape regional climates, this study focuses on the understudied role of local climatic variables in influencing near-surface air temperature (NST) in Ghana from 1981 to 2020. Based on ground observations, our findings reveal significant correlations between land surface temperature (LST) and NST before and after the identified breakpoint year of 2001. Additionally, we observe a reduction in precipitation post-2001. We also identify LST as the primary driver of NST and precipitation changes based on cause-effect analysis of multiple factors. Specifically, higher LST leads to decreased precipitation and increased NST, contributing to the increasing trend of NST over the last two decades. The insights are vital for developing targeted adaptation strategies, including integrated land and water management, sustainable agriculture, and effective interventions, directly supporting the United Nations Sustainable Development Goals (SDG) 13 (Climate Action) and SDG 15 (Life on Land). Moreover, the study provides evidence for promoting climate-smart agriculture to ensure food security (SDG 2). By integrating these findings into climate adaptation frameworks, policymakers and stakeholders can better address the unique challenges posed by climate variability in Ghana, ensuring more resilient and sustainable environmental management.